This article presents Design and Construction of Drug Sales and Inventory Applications at Sumber Sehat Pharmacy in Torjun District - Fauzan Prasetyo Eka Putra; Mubarok, Abdul Adim; Moh Syahdan; Muhammad Umar Mansyur (SEULANGA SYSTEM PUBLISHER, 2024)
This article presents the design and implementation of an application tailored to streamline the sales and supply processes of medicines at the Sumber Sehat Pharmacy located in the Torjun District. With the growing demand for efficient pharmaceutical services, the development of this application addresses the need for modernized systems to manage inventory, facilitate sales transactions, and enhance customer service. The application integrates user-friendly interfaces for both pharmacy staff and customers, ensuring ease of use and accessibility. Through the utilization of technology, the Sumber Sehat Pharmacy aims to optimize its operations, improve inventory management, and ultimately elevate the quality of healthcare services provided to the community. This study highlights the significance of technological innovation in the pharmaceutical sector and offers insights into the practical implementation of digital solutions within pharmacy settings.